2016
DOI: 10.5039/agraria.v11i4a5405
|View full text |Cite
|
Sign up to set email alerts
|

Cultivares de alface sob manejo orgânico no inverno e na primavera na Baixada Fluminense

Abstract: RESUMONo presente trabalho objetivou-se avaliar o comportamento de cultivares de alface conduzidas sob sistema de cultivo orgânico nas condições edafoclimáticas de Seropédica-RJ. Foram conduzidos dois experimentos independentes, em campo, em duas épocas do ano, no delineamento em blocos casualizados, com três repetições e doze plantas por parcela. No primeiro e segundo experimentos foram utilizados como tratamentos 22 e 25 cultivares de alface, respectivamente, pertencentes aos grupos crespa, lisa e americana.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Estes resultados são compatíveis e superiores aos relatados por Fiorini et al (2016) em estudo realizado neste mesmo município no período de primavera. Estes autores relataram para a cultivar Grand Rapids valores de BFC igual a 176,59 g planta -1 , enquanto que para a cultivar Elisa, os valores foram de 140,74 g planta -1 .…”
Section: Resultsunclassified
“…Estes resultados são compatíveis e superiores aos relatados por Fiorini et al (2016) em estudo realizado neste mesmo município no período de primavera. Estes autores relataram para a cultivar Grand Rapids valores de BFC igual a 176,59 g planta -1 , enquanto que para a cultivar Elisa, os valores foram de 140,74 g planta -1 .…”
Section: Resultsunclassified
“…The roselle (Hibiscus sabdariffa) was cultivated between the months of May and September in a Planosol in the Horticulture sector from the Federal Rural University of Rio de Janeiro -UFRRJ, in Seropédica -RJ, whose geographic coordinates are 22°44'38" S , 43º42'28'' W, at an altitude of 26 m and with the region climate being the Aw type, from the Köppen classification, with rainy summers and high temperatures, and between April and September the climate is milder and dry (Fiorini et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In line with these findings, Maia et al ( 2008) observed positive outcomes concerning this variable while evaluating the impact of biofertilizers prepared with nursery water. Similarly, Fiorini et al (2016) demonstrated significant results when assessing cultivars across two seasons under organic management in Baixada Fluminense, highlighting the seasonal influence on the development of plant head diameter (PHD).…”
Section: Plant Head Diameter (Phd; Cm)mentioning
confidence: 99%